Approaches to psychiatric assessment in epidemiological studies of children. (19th December 2008) - McClellan, J; Bresnahan, M A; Echeverria, D; Knox, S S; Susser, E
Abstract : An assessment protocol for the longitudinal measurement of developmental psychopathology in a population-based study of children and adolescents is proposed. The protocol is designed for use in a large cohort of up to 100 000 individuals followed from early gestation to 21 years of age. Although the protocol was constrained by specified methodological parameters, the recommendations may apply to other psychiatric epidemiological research designs. The issues and challenges inherent with psychiatric assessments in longitudinal epidemiological studies of children and adolescents are discussed.